The Intentionality of Logos, the True Transcendence of Dasein: A Dialogue on Heidegger’s Ontology in Father D. Stăniloae and J.-L. Marion - Isai, Daniel ca. 20./21. Jh. (Diakrisis, 2020)
This approach focuses on a convergence point between father Stăniloae’s theology and Jean-Luc Marion’s phenomenology, as concerns Heidegger’s ontology. The German philosopher launches a challenge as to the role that the Embodiment of Logos actually plays in human existence. According to him, the Incarnation event is for man only a corrective to the ontic, while father Stăniloae and the French philosopher consider that we are facing a true ontological reconfiguration of human existence. This is because the One who has stepped into the ontological field of the human being has the power to take man out of the being-toward-death paradigm and give him the opportunity to become being-toward-resurrection. Both father Stăniloae and Marion resort to areopagitic thinking, in which God is above the being, i.e. supra being, so He cannot be considered a being among others, even if He were considered a supreme being. At the same time, God is love because He is the Trinity of People and it is only through this reality that the human being gains more in terms of existence.